2019
DOI: 10.3758/s13428-019-01204-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic mappings between semantic categories and types of iconic representations in the manual modality: A normed database of silent gesture

Abstract: An unprecedented number of empirical studies have shown that iconic gestures-those that mimic the sensorimotor attributes of a referent-contribute significantly to language acquisition, perception, and processing. However, there has been a lack of normed studies describing generalizable principles in gesture production and in comprehension of the mappings of different types of iconic strategies (i.e., modes of representation; Müller, 2013). In Study 1 we elicited silent gestures in order to explore the impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 64 publications
(89 reference statements)
1
61
0
Order By: Relevance
“…There is a generalised assumption that the iconic strategies to represent a referent in gesture are idiosyncratic and thus variable. However, the results of the present study support recent evidence that spontaneous silent gestures may exhibit generalizable forms for many concepts across individuals (Ortega & Özyürek, 2016(Ortega & Özyürek, , 2019van Nispen et al, 2014). Importantly, some of these gestures overlap in form in varying degrees with conventionalised signs.…”
Section: Similarities In Iconic Form-meaning Mappings In Gesture and supporting
confidence: 89%
See 3 more Smart Citations
“…There is a generalised assumption that the iconic strategies to represent a referent in gesture are idiosyncratic and thus variable. However, the results of the present study support recent evidence that spontaneous silent gestures may exhibit generalizable forms for many concepts across individuals (Ortega & Özyürek, 2016(Ortega & Özyürek, , 2019van Nispen et al, 2014). Importantly, some of these gestures overlap in form in varying degrees with conventionalised signs.…”
Section: Similarities In Iconic Form-meaning Mappings In Gesture and supporting
confidence: 89%
“…Relevant to this study is the finding that individuals often resort to similar iconic strategies to represent the same concepts in silent gesture (Ortega & Özyürek, 2016(Ortega & Özyürek, , 2019Van Nispen et al, 2017). Ortega and Özyürek (2019) created a database of elicited silent gestures from Dutch adults and they found that participants employ remarkably similar strategies to depict referents. Through the implementation of specific types of iconic depictions and their combinations, participants systematically represent concepts across different semantic domains.…”
Section: Iconicity and Systematicity 1 In The Manual Modalitymentioning
confidence: 87%
See 2 more Smart Citations
“…The stimuli selection consisted of a two-stage procedure that involved i) collecting a set of iconic gestures that could be generalized across Dutch participants (silent gesture task). These gestures are a subset of a published database of 109 silent gestures (Ortega & Özyürek, 2019). Having collected these gestures, it was possible to ii) carry out a comparison between the form of each systematic gesture with its NGT sign equivalent (gesture-sign cross-comparison).…”
Section: Stimuli Selectionmentioning
confidence: 99%